Prevalence of Rotavirus among Iraqi children with diarrhea in Diyala province - Hameed, Ali (British Journal of Healthcare and Medical Research, 2021)
Background: Rotavirus is the most common cause of acute gastroenteritis in children below five years. Objectives: The aim of this study to evaluate the prevalence of rotavirus among children with diarrhea, the efficacy of Immuno Chromatography Assay (ICA) and Enzyme-linked Immunosorbent assay (ELISA) and evaluate the relationship between the demographic agent and clinical presentation associated with rotavirus. Material and Methods: A cross-sectional study was conducted at AL-Batool Teaching Hospital in Baqubah, from the first of April 2019 to 31 of March 2020, on (300) children with diarrhea below five years of age. The patients included (n=161, 53.6%) males and (n=139, 46.3%) females. The patient’s age, gender, living area, season, mode of feeding, source of water supply and sterilization, were collected through a questionnaire prepared for this study. The Rapid Test and ELISA are used for the detection of rotavirus in fecal specimens. Results: The rotavirus antigen was detected in (47.33%) stool specimens by the ELISA test and (59%) by ICA from (300) children with diarrhea and high infection in the age group between 13-24 months at the rate (49.40%). The highest infection rate in spring was (56.00%) and lower in summer (33.33%). The infection males more than females (42.24% vs. 39.57%). High significant infection among children living in rural areas (55.68%) compared to those living in urban areas (35.48%). According to the clinical features, the results showed the rate of rotavirus infection in children with fever was (54.90%), vomiting (42.03%), those suffering from severe dehydration (48.85) some dehydration 78 (46.15%), however, rotavirus infection was significant with fever only.